Integrated asset management framework for Australian wind farms - Shahid, M.; Mahamood, M.; Das, Narottam (2016)
© 2016 IEEE. Wind energy generation is one of the growing sector in the renewable energy industry. It is an effective though not an entirely reliable solution in generation of renewable energy without emitting dangerous greenhouse gases. The ever increasing power demand and the commitment from governments around the world, coupled with universal agreements such as the Kyoto Protocol to reduce the emission of greenhouse gases, has resulted in a rapid growth in wind energy generation. Australia is committed to generate 20% of its energy by renewable energy sources in 2020, wind energy growth in Australia is driven mainly by this mandatory renewable energy target. Assets in wind farm needs to be managed to ensure maximize energy production, reduce operating and maintenance cost as well as to minimize the downtime. Therefore, the purpose of this research is to develop an integrated asset management framework in order to ensure optimum service life while high asset value is retained.